Impact of postpartum weight change on metabolic syndrome and its components among women with recent gestational diabetes mellitus - Chadakarn Phaloprakarn; Sasiwan Suthasmalee; Siriwan Tangjitgamol (BMC, 2024)
Abstract Background While postpartum weight changes may affect the levels of metabolic parameters, the direct effects of weight changes in the postpartum period on changes in the prevalence rates of metabolic syndrome and its components remain unstudied. This study aimed to investigate the effects of postpartum weight changes between 6 weeks and 6 months on changes in the prevalence rates of metabolic syndrome and its components in women who have recently experienced gestational diabetes mellitus. Methods This prospective cohort study included 171 postpartum women with recent gestational diabetes mellitus, who underwent serial weight and metabolic risk factor assessments at 6 weeks and 6 months postpartum. Weight changes between these time points were classified as weight loss (> 2 kg), weight stability (± 2 kg), or weight gain (> 2 kg). Metabolic syndrome comprised the following metabolic risk factors: large waist circumference, elevated blood pressure, elevated fasting plasma glucose levels, high triglyceride levels, and low high-density lipoprotein cholesterol levels. Results Of the 171 women in our cohort, 30 women (17.5%) lost > 2 kg of body weight, while 85 (49.7%) maintained a stable weight and 56 (32.8%) gained > 2 kg. The weight loss group experienced significant changes in the prevalence rates of the following metabolic risk factors compared to the weight stability and weight gain groups: large waist circumference (% change: − 26.7 vs − 5.9 vs 5.4, respectively; p = 0.004), elevated fasting plasma glucose levels (% change: − 3.4 vs 18.9 vs 26.8, respectively; p = 0.022), and high triglyceride levels (% change: − 30.0 vs 0 vs − 7.2, respectively; p = 0.024). A significantly greater decrease in the prevalence of metabolic syndrome was also found in the weight loss group than in the other two groups (% change: − 20.0 vs 11.8 vs 14.2, respectively; p = 0.002). Conclusions Weight changes from 6 weeks to 6 months postpartum significantly altered the prevalence rates of metabolic syndrome and its components in women with recent gestational diabetes mellitus. Early postpartum weight loss can reverse metabolic risk factors and reduce the prevalence of metabolic syndrome. Trial registration Thai Clinical Trials Registry: Registration no. TCTR20200903001. Date of registration: September 3, 2020. Date of initial participant enrolment: September 7, 2020.